Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Problem Based Learning pada Pembelajaran Tematik Terpadu di Kelas IV SD - Zayani, Hayati; Indrawati, Tin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This research is motivated by the less optimal integrated thematic learning that results in students not understanding the material so that it impacts on learning outcomes. This study aims to describe the Improved Integrated Thematic learning outcomes Using the Problem Based Learning (PBL) Model for Class IV students of SDN 01 Pasar Laban Bungus, Padang City. This type of research is CAR with qualitative and quantitative approaches. The research data are in the form of observations and tests. The study was carried out in two cycles. The research subjects were teachers and grade IV students. The results of the study in terms of RPP cycle I meeting I and II, the second cycle is 77.8% (C), 83.3 (B), 97.2% (SB). The activities of teachers in cycle I and II, cycle II were 71.9% (C), 84.4% (B), 93.7% (SB). The activities of students in cycle I and II, cycle II were 75% (C), 81.2% (B), 93.75% (SB). Aspects of attitude in the first cycle of students reflect the main attitudes of independence and do not reflect the attitude of mutual cooperation, and integrity. Cycle II students reflect mutual cooperation, integrity and independence. The first aspect of knowledge cycle is 82.7 (B), second cycle is 89.1 categories (B). The skill aspect of the first cycle is 82.9 (B), the second cycle is 92.8 categories (SB).